Social Correlates of Church Attendance in Three European Catholic Countries - Conway, Brian (Review of religious research, 2013)
The sociology of religion literature recognizes secularization as an uneven process complicated by individual and country-level variables. However, considerably less attention has been given to how correlates of church attendance vary across divergent settings within a single religious denomination. Employing recent data from Belgium, Ireland, and Slovenia, we test whether the belief, ideological support for the church, and religious commitment correlates of religious behaviour are similar across these Catholic countries and whether there are any remaining country effects influencing church attendance. The results of ordered logit regression models show, on the one hand, the correlates of church attendance are basically the same across the three countries and, on the other, that country effects remain even when controlling for the key explanatory variables and other covariates. These empirical findings suggest the need to develop a more contextual-based understandings of secularization, focusing on the influence of cultural factors operative in nationally-specific settings.